Calix[4]arene‐based Multifunctional Ligand as Potent Protein Binding Agent. (11th September 2018) - Esmaielzade Rostami, Mahshid; Gorji, Banafsheh; Zadmard, Reza
Abstract : In this work, a new protein binding agent based on multifunctional calix[4]areneCP has been synthesized by a one‐pot four‐component reaction. Protein binding affinity of designed ligand (CP ) was investigated in physiological buffer (pH = 7.4) by fluorescence quenching method and revealed considerable binding affinity betweenCP and β‐lactoglobulin (BLG). The three‐dimensional (3D) fluorescence measurements indicated that binding ofCP to BLG did not influence on BLG conformation. Furthermore, the effect of various biologically important metal ions on the binding constant ofCP with BLG was investigated. Abstract :